THE FIRST RECORD OF Holothuria (Semperothuria) Roseomaculata KERR, 2013 (Echinodermata: Holothuroidea) IN INDONESIA - Setyastuti, Ana (Marine Research in Indonesia, 2018)
This paper documents the first record of Holothuria (Semperothuria) roseomaculata Kerr, 2013 (Echinodermata: Holothuroidea) from Indonesia. A freshly salted specimen was collected from fishers in Sumbawa, West Nusa Tenggara, Indonesia. This species was previously recorded from Yap and Chuuk States in the Federated States of Micronesia, Papua New Guinea, Palau, Okinawa-Japan, Sabah, Borneo-Malaysia, Solomon Islands, Vanuatu and New Caledonia. Reference material has been deposited in the Reference Collection of the Research Center for Oceanography, Indonesian Institute of Sciences in Jakarta, Indonesia.